2018
DOI: 10.3791/56952
|View full text |Cite
|
Sign up to set email alerts
|

<em>In Vivo</em> Single-Molecule Tracking at the Drosophila Presynaptic Motor Nerve Terminal

Abstract: An increasing number of super-resolution microscopy techniques are helping to uncover the mechanisms that govern the nanoscale cellular world. Single-molecule imaging is gaining momentum as it provides exceptional access to the visualization of individual molecules in living cells. Here, we describe a technique that we developed to perform single-particle tracking photo-activated localization microscopy (sptPALM) in Drosophila larvae. Synaptic communication relies on key presynaptic proteins that act by dockin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Syntaxin-1 is organized as nanoclusters in the NMJs of Drosophila larvae (Bademosi et al, 2017;Ullrich et al, 2015). To understand how activity-dependent neurotransmitter release alters the nanocluster organization of syntaxin-1 in the presynaptic membrane, Bademosi et al (2017Bademosi et al ( , 2018aBademosi et al ( , 2018b) developed a new protocol to image syntaxin-1-mEos2 in the NMJs of fixed and live third instar Drosophila larvae (Fig. 2).…”
Section: Syntaxin-1 Dynamics In Neuronal Synapsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Syntaxin-1 is organized as nanoclusters in the NMJs of Drosophila larvae (Bademosi et al, 2017;Ullrich et al, 2015). To understand how activity-dependent neurotransmitter release alters the nanocluster organization of syntaxin-1 in the presynaptic membrane, Bademosi et al (2017Bademosi et al ( , 2018aBademosi et al ( , 2018b) developed a new protocol to image syntaxin-1-mEos2 in the NMJs of fixed and live third instar Drosophila larvae (Fig. 2).…”
Section: Syntaxin-1 Dynamics In Neuronal Synapsesmentioning
confidence: 99%
“…This technique allows for the quantification of the size distribution of protein clusters on the plasma membrane (Klar and Hell, 1999;Sieber et al, 2006;Sieber et al, 2007;van den Bogaart et al, 2011). PALM allows for the characterization of the size and distribution of protein clusters in fixed and live cells and allows single particle tracking (sptPALM) in live cells (Bademosi et al, 2018a;Bademosi et al, 2017;Bademosi et al, 2018b;Manley et al, 2008;Vanhauwaert et al, 2017;Yang et al, 2012). Unlike PALM, stochastic optical reconstruction microscopy (STORM) uses photoswitchable organic fluorophores to immunolabel endogenous proteins (Bar-On et al, 2012;Rust et al, 2006).…”
Section: Box 1: a Brief Overview Of Imaging Techniquesmentioning
confidence: 99%
“…Here, synaptic vesicles in the fly larval neuromuscular junction are more readily docked and primed compared to chromaffin cells, suggesting important differences in the physiological relevance of the two systems for studying neurotransmission. We recently described single molecule imaging in intact motor nerve terminals of filleted Drosophila larvae (Bademosi et al, 2016(Bademosi et al, , 2018a. In that study we tagged the pre-synaptic protein syntaxin1A (Sx1a) with photoconvertible mEos2 and found that genetic stimulation of motoneurons resulted in increased mobility of Sx1A in the motor nerve terminals, suggesting increased mobilization of the presynaptic machinery when neurons are activated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have described single molecule imaging in motor nerve terminals of filleted larvae of the fruit fly Drosophila melanogaster (Bademosi et al, 2018a, 2016). In that study we tagged the pre-synaptic protein syntaxin1A (Sx1a) with photoconvertible mEos2 and found that genetic activation of motoneurons resulted in increased mobility of Sx1A in the motor nerve terminals, suggesting increased mobilization of the presynaptic machinery when neurons are activated.…”
Section: Introductionmentioning
confidence: 99%